Neurostimulation for Functional Recovery After Traumatic Brain Injury: Current Evidence and Future Directions for Invasive Surgical Approaches. Issue 6 (7th December 2022) - Tiefenbach, Jakov; Chan, Hugh H.; Machado, Andre G.; Baker, Kenneth B.
Abstract : We aim to provide a comprehensive review of the current scientific evidence supporting the use of invasive neurostimulation in the treatment of deficits associated with traumatic brain injury (TBI), as well as to identify future directions for research and highlight important questions that remain unaddressed. Neurostimulation is a treatment modality with expanding applications in modern medical practice. Targeted electrical stimulation of specific brain regions has been shown to increase synaptogenesis and enhance structural reorganization of neuronal networks. This underlying therapeutic effect might be of high value for patients suffering from TBI because it could modulate neuronal connectivity and function of areas that are partially or completely spared after injury. The current published literature exploring the application of invasive neurostimulation for the treatment of functional deficits associated with TBI is scarce but promising. Rodent models have shown that targeted stimulation of the hippocampus or connecting structures can result in significant cognitive recovery, while stimulation of the motor cortex and deep cerebellar nuclei is associated with motor improvements. Data from clinical studies are extremely limited; single-patient reports and case series found neurostimulation to be effective in relieving motor symptoms, improving visuospatial memory, and supporting emotional adjustment. Looking forward, it will be important to identify stimulation targets and paradigms that can maximize improvement over multiple functional domains. It will also be important to corroborate the observed behavioral improvements with histological, electrophysiological, and radiological evidence. Finally, the impact of biological variables such as sex and age on the treatment outcomes needs to be explored.